Effect of Influent Concentration and Hydraulic Retention Time on the Performance of an Anaerobic Hybrid Reactor Treating Wastewater from Washing of Sugarcane Bagasse - Sawasdikul, Jeeraporn; Rodprapakorn, Mangkorn; Nitayapat, Nuttakan; Panichnumsin, Pornpan (Agriculture and Natural Resources, 2015)
In the pulp and paper industry, several hundred thousand tonnes of sugarcane bagasse may be received from a sugar mill annually during December and May and is stored using a wet storage method in the bagasse yard for use as raw material throughout the year. This method of storing bagasse generates approximately 7,000 m3 of wastewater. Anaerobic treatment is an effective means of biodegradation of organic matter in wastewater and biogas that can be used to produce an alternative fuel. This work investigated the effects of the influent concentration and hydraulic retention time (HRT) on the treatment of bagasse wash wastewater. An anaerobic hybrid reactor (AHR) was chosen and the chemical oxygen demand (COD) removal efficiency and biogas yield were determined to evaluate the optimum operating parameters. Two laboratory scale AHRs (A1 and A2) were operated at a constant HRT of 2 d (A1) and 4 d (A2) and they were fed with influent concentrations of 5 to 20 g COD.L-1. The results showed that the COD removal efficiencies of A1 and A2 were in the range 76–93% and 91–98%, respectively. The biogas yield of A2 was higher than that of A1 throughout the course of the experiment. The biogas yields of A1 (YA1) and A2 (YA2) were 0.498 and 0.540 L.g-1 CODadded, at an influent concentration of 20 g COD.L-1; they increased linearly with the concentration in the wastewater influent and it was found that YA1 = 0.0509 (influent COD) + 0.1683 equation with the coefficient of determination (r2) = 0.9223 and YA2 = 0.0390 (influent COD) + 0.2791 with r2 = 0.8921.The methane content of the biogas from both reactors was as high as 70%.